Investigation of p‐contact layers for BeZnSeTe/MgZnCdSe optical devices on InP substrates. Issue 7 (25th March 2014) - Takamatsu, Shingo; Nomura, Ichirou; Kobayashi, Toshiki; Murakami, Keisuke; Shiraishi, Tomohiro; Kishino, Katsumi
Abstract: ZnTe and ZnSeTe p‐contact layers were investigated for use in BeZnSeTe/MgZnCdSe optical devices on InP sub‐strates. The contact resistances (Rc ) of Au electrodes to N‐doped p‐ZnTe and p‐ZnSeTe contact lay‐ers were evaluated using the circular transmission line model (c‐TLM) method. A lower Rc (3.1×10 ‐3 Ωcm 2 ) was obtained for the ZnSeTe p‐contact sample than for the ZnTe sample (6.3×10 ‐3 Ωcm 2 ). BeZnSeTe/MgZnCdSe yellow‐light‐emitting devices with a ZnTe or ZnSeTe p‐contact layer grown on InP substrates were characterized. A comparison of the current‐voltage (I‐V) characteristics of these devices showed that the turn‐on voltage of the ZnSeTe contact device was about 4 V lower than that of the ZnTe device. From the aging characteristics of these devices under direct‐current injection at room temperature, it was shown that the lifetime of the ZnSeTe contact device was 30 times longer than that of the ZnTe contact device. These results show that a ZnSeTe contact layer is more suitable for BeZnSeTe/MgZnCdSe optical devices on InP substrates than a ZnTe contact layer. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)